Typography of Culture-Specific Scripts in Interior Branding: Preliminary Data from Indonesian Consumers in the Case of Ethnic Restaurants - Aditya Bayu Perdana; Sri Maharani Budi Haswati; Hana Faza Surya Rusyda; Togar Mulya Raja (ITB Journal Publisher, DRPM ITB, 2025)
Anecdotal accounts suggest that Indonesians perceive culture-specific scripts on typographic artefacts in restaurants as a sign of authenticity and quality. This study examined this notion through qualitative literature synthesis followed by a preliminary quantitative survey. The literature synthesis foregrounded comparable cases where typographic attributes and script choice have been found to influence consumer perception, which shows that the phenomenon is not isolated to Indonesia. The preliminary quantitative survey used a simple frequency analysis of four fictional restaurant logotypes (Japanese, Korean, Balinese, and Javanese, respectively) to determine values that Indonesian consumers perceive in culturally authentic typography (prominent use of indigenous, culture-specific scripts). The majority of respondents perceived culturally authentic typography as representing high-value restaurants in terms of price, food quality, and atmosphere. More respondents associated Japanese/Korean typography with high-quality Japanese/Korean restaurants, compared to respondents who associated Balinese/Javanese typography with high-quality Balinese/Javanese restaurants. More respondents related culturally authentic typography with higher prices, followed by better restaurant atmosphere, and better food quality. These findings confirm that Indonesian consumers perceive culture-specific scripts as indicative of higher brand values to some degree. More rigorous research is warranted to validate these results.